Review of Brain Computer Interface Technology in the Treatment of Motor Dysfunction after Stroke - Yulian ZHU; Sijie LIANG (康复学报)
We had reviewed the researches on brain computer interface (BCI) technology in the treatment of motor dysfunction after stroke by scholars from domestic and foreign, to explain in four aspects, such as definition and classification, working principle and theoretical basis in clinical treatment, specific clinical application and the existing problems. BCI is a communication system technology that combines hardware and software, which enables human beings to interact with the surrounding environment without being affected by peripheral nerves and muscles by using the control signals generated by EEG activities. It will help patients achieve certain functions and improve the quality of life by controlling the external devices. BCI has the characteristics of high safety, convenient treatment and good effect. According to the location of signal acquisition, BCI is divided into non-invasive BCI and invasive BCI, while the non-invasive BCI is used more commonly in clinic. The work flow of BCI in treating stroke patients could be roughly divided into five steps: signal acquisition, preprocessing or signal enhancement, feature extraction, classification and control interface. At present, BCI technology has been applied to treat stroke patients in the upper limbs, hands, lower limbs or walking dysfunction. It is mainly through the methods of recovery and replacement to promote the brain plasticity of stroke patients, so as to help the motor function of stroke patients in rehabilitation. However, there are still some deficiencies of BCI technology in clinical, such as the quality of BCI signal acquisition, the parameter setting of BCI treatment exercise prescription, and the selection difficulties of BCI treatment mode. In conclusion, BCI has a good effect in the treatment of post-stroke motor dysfunction, which provided a new and effective reference to improve the clinical effect of BCI, but the next step is to further study the existing problems and the specific mechanism in order to improve the clinical effect of BCI.